Pattern transfer plate, pattern transfer method, and solar cell

By using a pattern transfer plate, including a transfer substrate, an adhesive layer, and a temperature-controlled adhesive reversible material coating, the problem of limited resolution and precise control of electrode shape in photovoltaic metallization technology is solved, and high-quality gate line preparation is achieved and high battery conversion efficiency.

CN119348290AActive Publication Date: 2025-01-24TRINA SOLAR CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411694331.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-24
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing photovoltaic metallization technology has problems such as limited resolution and electrode shape control, high equipment production capacity and stability requirements, easy degrid and oxidation of copper grid lines, difficult yield control, and easy pollution of the environment.

Method used

The pattern transfer plate is used, including the transparent plate, the adhesive layer, and the temperature -controlled viscosity coating. By regulating the temperature of the coating, the adverse resistance is realized, the laser barriers and slurry debris problems are solved, and production costs are reduced.

Benefits of technology

Achieve high-quality gate line preparation, break through the line width limit, increase the aspect ratio, reduce the shading area, improve the battery conversion efficiency, reduce the slurry consumption, and avoid the specific transparent transfer carrier material use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119348290A_ABST
    Figure CN119348290A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solar cells, and mainly provides a pattern transfer printing plate, a pattern transfer printing method and a solar cell. The pattern transfer printing plate comprises a transfer printing substrate, a bonding layer and a coating, the transfer printing substrate is provided with a plurality of accommodating grooves; the accommodating groove is used for accommodating electrode slurry; the bonding layer is located on the surface of the containing groove. The bonding layer comprises a bonding agent; the coating is positioned on the surface of the bonding layer; the coating comprises a temperature-control viscous reversible material; the temperature-control viscous reversible material comprises a block copolymer, a cross-linking agent and a free radical initiator; the molar ratio of the cross-linking agent to the free radical initiator in the coating is gradually increased in the direction away from the transfer printing substrate. According to the technical scheme, the pattern transfer printing plate solves the problems of laser barriers and no slurry chippings, and the production cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to a pattern transfer plate, a pattern transfer method, and a solar cell. Background Art

[0002] Photovoltaic (solar) cell metallization technology refers to the process of forming a conductive metal layer on the surface of the cell. These metal layers are used to collect and transmit the current generated by the photovoltaic cell. Metallization is a key step in the manufacture of photovoltaic cells because it directly affects the efficiency and performance of the cell. The commonly used photovoltaic metallization technologies include screen printing, electroplating, and laser transfer.

[0003] Screen printing technology is low-cost and suitable for large-scale production, but its resolution and precise control of electrode shape are limited. Electroplating technology can achieve low-cost and high-efficiency metallization, but it requires the formation of a conductive seed layer on the battery surface in advance. There are problems such as high requirements for equipment production capacity and stability, copper grid lines are easy to debond and oxidize, yield is difficult to control, and it is easy to pollute the environment. Laser transfer is a non-contact printing technology that coats the required slurry on a specific flexible light-transmitting material and uses a high-power laser beam to graphically scan and transfer the slurry from the flexible light-transmitting material to the battery surface to form grid lines and achieve high-precision electrode patterns; however, the cost of flexible films is relatively high, and laser transfer requires precise control of the matching relationship between slurry parameters and laser power. The technical barriers are high, and the slurry is prone to splashing and slurry debris problems, which affect the quality of the grid lines. In addition, lasers can only move in a straight line at present, and their application range is limited.

[0004] It should be noted that the above content is not necessarily prior art, nor is it intended to limit the scope of patent protection of this application. Summary of the invention

[0005] The embodiments of the present application provide a pattern transfer plate, a pattern transfer method, and a solar cell to solve or alleviate the above-mentioned technical problems. The pattern transfer plate of the technical solution of the present application solves the problems of laser barriers and no slurry debris, and can reduce production costs.

[0006] In a first aspect, an embodiment of the present application provides a pattern transfer plate, comprising: A transfer substrate, wherein the transfer substrate has a plurality of receiving grooves; the receiving grooves are used to receive electrode slurry; An adhesive layer, the adhesive layer is located on the surface of the receiving groove; the adhesive layer includes an adhesive; A coating, wherein the coating is located on the surface of the bonding layer; the coating comprises a temperature-controlled viscous reversible material; the temperature-controlled viscous reversible material comprises a block copolymer, a crosslinking agent and a free radical initiator; the molar ratio of the crosslinking agent to the free radical initiator in the coating gradually increases in a direction away from the transfer substrate; the block copolymer comprises a block copolymer containing a poly(ethylene oxide-propylene oxide-ethylene oxide) group; and the crosslinking agent comprises an organic acid ester containing a disulfide bond.

[0007] Optionally, the coating comprises at least a first sub-coating layer and a second sub-coating layer stacked in sequence in a direction away from the transfer substrate; The molar ratio of the crosslinking agent to the free radical initiator in the first sub-coating layer is smaller than the molar ratio of the crosslinking agent to the free radical initiator in the second sub-coating layer.

[0008] Optionally, the coating comprises a first sub-coating, a third sub-coating, and a second sub-coating which are sequentially stacked in a direction away from the transfer substrate; wherein the molar ratio of the crosslinking agent to the free radical initiator in the first sub-coating is less than the molar ratio of the crosslinking agent to the free radical initiator in the third sub-coating; The molar ratio of the crosslinker to the free radical initiator in the third sub-coating is less than the molar ratio of the crosslinker to the free radical initiator in the second sub-coating.

[0009] Optionally, the block copolymer containing poly(ethylene oxide-propylene oxide-ethylene oxide) groups includes poly(styrene-isoprene-styrene)-poly(ethylene oxide-propylene oxide-ethylene oxide) block copolymer.

[0010] Optionally, the disulfide bond-containing organic acid ester includes one or both of disulfide bond-containing diacrylate and disulfide bond-containing dibutyl acrylate.

[0011] Optionally, the free radical initiator includes one or both of azobisisobutyronitrile and azobisisoheptanenitrile.

[0012] Optionally, the temperature-controlled viscosity reversible material further includes an aminosilane coupling agent.

[0013] Optionally, the aminosilane coupling agent includes one or both of γ-aminopropyltriethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.

[0014] Optionally, the molar ratio of the crosslinking agent to the block copolymer is 0.05-0.3.

[0015] Optionally, the adhesive comprises an aminosilane adhesive.

[0016] Optionally, the thickness of the bonding layer is 0.1-1 μm, and the thickness of the coating is 5-15 μm.

[0017] In a second aspect, an embodiment of the present application provides a pattern transfer method, comprising: A pattern transfer plate is provided, the pattern transfer plate comprising a transfer substrate having a plurality of receiving grooves, and a bonding layer and a coating layer sequentially stacked in the receiving grooves; the bonding layer comprises a bonding agent; the coating layer comprises a temperature-controlled viscosity reversible material; the temperature-controlled viscosity reversible material comprises a block copolymer, a crosslinking agent and a free radical initiator; the molar ratio of the crosslinking agent to the free radical initiator in the coating layer gradually increases in a direction away from the transfer substrate; the block copolymer comprises a block copolymer containing a poly(ethylene oxide-propylene oxide-ethylene oxide) group; the crosslinking agent comprises an organic acid ester containing a disulfide bond; Heating the coating to 80° C.-100° C. to increase the viscosity of the coating; Filling the electrode slurry into the containing tank having the coating on the surface; The pattern transfer plate filled with the electrode slurry is inverted on the substrate, the coating is heated to above 120° C. to reduce the viscosity of the coating, and the electrode slurry in the containing tank is transferred to the substrate.

[0018] Optionally, when the coating is at 80°C-100°C, the viscosity of the coating is 100-500 Pa·s; When the coating is at a temperature of 120° C. or higher, the coating has a viscosity of 10-50 Pa·s.

[0019] In a third aspect, an embodiment of the present application provides a solar cell, comprising a gate line electrode, wherein the gate line electrode is prepared using a pattern transfer plate provided in any one of the above items, and / or the gate line electrode is prepared by a pattern transfer method provided in any one of the above items.

[0020] The above technical solution adopted in the embodiment of the present application may have the following advantages: In an embodiment of the present application, the pattern transfer plate includes an adhesive layer formed by an adhesive and a coating formed by a temperature-controlled viscous reversible material. The adhesive layer is located between the transfer substrate and the coating, and the adhesive layer can strengthen the bonding effect between the transfer substrate and the coating, and prevent the coating from detaching from the transfer substrate after the polymer in the coating is de-crosslinked. The viscosity of the coating is affected by temperature, and the viscosity reversible performance is achieved by regulating the temperature of the coating, which not only makes the coating recyclable, but also the prepared grid line has good quality, breaks through the grid line width limit prepared by the current process, achieves a better aspect ratio, reduces the shading area, improves the battery conversion efficiency, reduces the slurry consumption, and does not need to use a specific transparent transfer carrier material as a substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the multiple drawings represent the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings only depict some embodiments disclosed in the present application and should not be regarded as limiting the scope of the present application.

[0022] Figure 1 is a schematic structural diagram of a pattern transfer plate provided in an embodiment of the present application; Figure 2 is a schematic structural diagram of a pattern transfer plate provided in an embodiment of the present application; Figure 3 A schematic diagram of transferring an electrode slurry to a substrate in a pattern transfer method provided in an embodiment of the present application.

[0023] Description of reference numerals: 10. Transfer substrate; 11. Receiving groove; 20. Adhesive layer; 30. Coating layer; 31. First sub-coating layer; 32. Second sub-coating layer; 33. Third sub-coating layer; 40. Electrode slurry; 50. Base. DETAILED DESCRIPTION

[0024] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. In the accompanying drawings, for clarity, the sizes of layers, regions, elements and their relative sizes may be exaggerated. Wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limitations on the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be combined with each other.

[0025] It should be understood that when an element or layer is referred to as "on", "under", "adjacent to", "connected to" or "coupled to" other elements or layers, it may be directly on, adjacent to, connected to or coupled to other elements or layers, or there may be intervening elements or layers. In contrast, when an element is referred to as "directly on", "under", "directly adjacent to", "directly connected to" or "directly coupled to" other elements or layers, there are no intervening elements or layers. It should be understood that although the terms first, second, third, etc. may be used to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings of the present disclosure, the first element, component, region, layer or part discussed below may be represented as a second element, component, region, layer or part. When a second element, component, region, layer or section is discussed, it does not necessarily mean that the first element, component, region, layer or section must be present in the present disclosure.

[0026] In this application, unless otherwise clearly specified and limited, the terms "set", "install", "connect", "connect", "fix" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0027] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein, for example. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0028] Hereinafter, exemplary embodiments according to the present application will be described in more detail with reference to the accompanying drawings. It should be noted that these exemplary embodiments can be implemented in many different forms and should not be construed as being limited to the embodiments described herein.

[0029] like Figure 1 to Figure 2 As shown, the embodiment of the present application provides a pattern transfer plate, comprising: The transfer substrate 10 has a plurality of receiving grooves 11; the receiving grooves 11 are used to receive the electrode slurry 40; The adhesive layer 20 is located on the surface of the receiving groove 11; the adhesive layer 20 includes an adhesive; The coating 30 is located on the surface of the bonding layer 20; the coating 30 includes a temperature-controlled viscous reversible material; the temperature-controlled viscous reversible material includes a block copolymer, a cross-linking agent and a free radical initiator; the molar ratio of the cross-linking agent to the free radical initiator in the coating 30 gradually increases in a direction away from the transfer substrate 10; the block copolymer includes a block copolymer containing a poly (ethylene oxide-propylene oxide-ethylene oxide) group; the cross-linking agent includes an organic acid ester containing a disulfide bond.

[0030] In an embodiment of the present application, the pattern transfer plate includes an adhesive layer formed by an adhesive and a coating formed by a temperature-controlled viscous reversible material. The adhesive layer is located between the transfer substrate and the coating, and the adhesive layer can strengthen the bonding effect between the transfer substrate and the coating, and prevent the coating from detaching from the transfer substrate after the polymer in the coating is de-crosslinked. The viscosity of the coating is affected by temperature, and the viscosity reversible performance is achieved by regulating the temperature of the coating, which not only makes the coating recyclable, but also the prepared grid line has good quality, breaks through the grid line width limit prepared by the current process, achieves a better aspect ratio, reduces the shading area, improves the battery conversion efficiency, reduces the slurry consumption, and does not need to use a specific transparent transfer carrier material as a substrate.

[0031] In the process of preparing the electrode grid line, when the temperature is 80℃-100℃, the free radical initiator releases free radicals, thereby promoting the cross-linking reaction between the organic acid ester containing disulfide bonds (-SS-) and the block copolymer containing poly (ethylene oxide-propylene oxide-ethylene oxide) groups, forming a three-dimensional network structure, restricting the movement of the polymer chain, and enhancing the cohesion of the coating, so that the coating can effectively transfer stress during the bonding process, improve the bonding performance of the coating, and make the electrode slurry bonded by the coating. When the temperature is greater than or equal to 120℃, the disulfide bonds (-SS-) of the organic acid ester containing disulfide bonds are broken, the three-dimensional network structure is de-crosslinked, and the viscosity of the coating is reduced, which is conducive to transferring the electrode slurry from the holding tank to the substrate and achieving reversible viscosity.

[0032] In the embodiment of the present application, the molar ratio of the crosslinker to the free radical initiator in the coating gradually increases in the direction away from the transfer substrate. On the side of the coating close to the transfer substrate, the molar ratio of the crosslinker to the free radical initiator is small, its viscosity is less affected by temperature, and the viscosity is also small, mainly bonded to the transfer substrate through the bonding layer; on the side of the coating away from the transfer substrate, the molar ratio of the crosslinker to the free radical initiator is large, its viscosity is greatly affected by temperature, when the temperature is 80℃-100℃, the viscosity is large, the electrode slurry can be firmly bonded, when the temperature is greater than or equal to 120℃, the viscosity is small, and the electrode slurry can be released.

[0033] In some embodiments, Figure 1 As shown, the coating 30 at least includes a first sub-coating 31 and a second sub-coating 32 sequentially stacked in a direction away from the transfer substrate 10; The molar ratio of the crosslinking agent to the free radical initiator in the first sub-coating layer 31 is smaller than the molar ratio of the crosslinking agent to the free radical initiator in the second sub-coating layer 32 .

[0034] In some embodiments, Figure 2 As shown, the coating 30 includes a first sub-coating 31, a third sub-coating 33, and a second sub-coating 32 which are sequentially stacked in a direction away from the transfer substrate 10; Wherein, the molar ratio of the crosslinking agent to the free radical initiator in the first sub-coating layer 31 is less than the molar ratio of the crosslinking agent to the free radical initiator in the third sub-coating layer 33; The molar ratio of the crosslinking agent to the free radical initiator in the third sub-coating layer 33 is smaller than the molar ratio of the crosslinking agent to the free radical initiator in the second sub-coating layer 32 .

[0035] In an optional embodiment, when the coating includes a first sub-coating and a second sub-coating stacked in sequence along a direction away from the transfer substrate, the molar ratio of the cross-linking agent to the free radical initiator in the first sub-coating is 10-20 (for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20), and the molar ratio of the cross-linking agent to the free radical initiator in the second sub-coating is 12.5-33 (for example, 12.5, 13, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33).

[0036] In an optional embodiment, when the coating includes a first sub-coating, a third sub-coating, and a second sub-coating stacked in sequence along a direction away from the transfer substrate, the molar ratio of the cross-linking agent to the free radical initiator in the first sub-coating is 10-12.5 (for example, 10, 11, 12, 12.5), the molar ratio of the cross-linking agent to the free radical initiator in the third sub-coating is 12.5-20 (for example, 12.5, 13, 14, 15, 16, 17, 18, 19, 20), and the molar ratio of the cross-linking agent to the free radical initiator in the second sub-coating is 16.66-33 (for example, 16.66, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33).

[0037] In an optional embodiment, the coating may also include four sub-coating layers, five sub-coating layers or more sub-coating layers, and the molar ratio of the crosslinking agent to the free radical initiator in each sub-coating layer increases successively in a direction away from the transfer substrate.

[0038] In some embodiments, the block copolymer containing poly(ethylene oxide-propylene oxide-ethylene oxide) groups includes poly(styrene-isoprene-styrene)-poly(ethylene oxide-propylene oxide-ethylene oxide) block copolymer.

[0039] In the poly(styrene-isoprene-styrene)-poly(ethylene oxide-propylene oxide-ethylene oxide) block copolymer, the poly(ethylene oxide-propylene oxide-ethylene oxide) group (PEO-PPO-PEO) has good hydrophilicity and temperature responsiveness, and can undergo cross-linking reaction with organic acid esters containing disulfide bonds (-SS-) under the action of free radical initiators; the styrene segments in the poly(styrene-isoprene-styrene) group (SIS) give the block copolymer hardness and rigidity, and the isoprene segments give the block copolymer elasticity, thereby providing the coating with good flexibility and certain strength. In addition, the SIS group physically adsorbs to the surface of the bonded material through van der Waals forces, and the PEO-PPO-PEO group interacts with the polar groups on the surface of the bonded material through hydrogen bonds, thereby improving the viscosity of the coating.

[0040] In some embodiments, the disulfide bond-containing organic acid ester includes one or both of a disulfide bond-containing bisacrylate and a disulfide bond-containing bisbutenoate.

[0041] The two cross-linking agents have higher reactivity. Under the action of free radical initiators, double bonds are easily opened to form free radical active centers, and effective cross-linking structures can be formed in a short time. Moreover, the molecular structures of these two cross-linking agents are small, similar to the polarity of block copolymers, and have good compatibility with block copolymers. They can be evenly dispersed in the system to ensure that the cross-linking reaction is carried out evenly throughout the coating. Other acid esters containing disulfide bonds (for example, certain aromatic acid esters containing disulfide bonds) have poor compatibility with non-polar segments in block copolymers due to their larger molecular structures and stronger polarity, and are prone to phase separation, thereby affecting the performance of the coating. In addition, the molecular structures of these two cross-linking agents have a small space and moderate bond energy of disulfide bonds, and can be quickly de-cross-linked (within 2-5 seconds) at 120 degrees, which can meet the requirements of quickly achieving non-stickiness.

[0042] In some embodiments, the free radical initiator includes one or both of azobisisobutyronitrile and azobisisoheptanenitrile.

[0043] This type of initiator can decompose and generate free radicals during the heating process. It has high activity and initiation efficiency. It can initiate a free radical polymerization reaction between the crosslinker and the block copolymer, thereby promoting the formation of a crosslinked network.

[0044] In some embodiments, the temperature-controlled viscosity reversible material further includes an aminosilane coupling agent.

[0045] Aminosilane coupling agent is a tackifier that improves the wettability and affinity between the coating and the surface of the bonded material. The amino group (-NH2) in the aminosilane coupling agent can interact with the oxygen atoms (poly(ethylene oxide-propylene oxide-ethylene oxide) groups contain a large number of ether bonds (-O-)) or phenyl groups (some block copolymers contain phenyl groups) in the block copolymer (for example, forming hydrogen bonds), which can improve the bonding strength of the coating and improve the durability of the coating.

[0046] In some embodiments, the aminosilane coupling agent includes one or both of γ-aminopropyltriethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.

[0047] γ-Aminopropyltriethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane contain alkoxy groups (e.g., ethoxy (-OC2H5), methoxy (-OCH3)), which can react with functional groups such as hydroxyl groups on the surface of the bonded material, thereby further improving the adhesion of the coating. In some embodiments, the molar ratio of crosslinker to block copolymer is 0.05-0.3.

[0048] When the amount of cross-linking agent is too much, too many cross-linking points will be formed in the polymer, which may cause the polymer to form a large number of cross-linked structures, affecting the subsequent de-cross-linking reaction; when the amount of cross-linking agent is too little, it will not form enough cross-linking points, which will reduce the connection inside the coating, reduce the cohesion and bonding strength of the coating, and affect the stability and physical properties of the coating. When the molar ratio of the cross-linking agent to the block copolymer is 0.05-0.3, it can ensure the formation of sufficient cross-linking points and improve the stability and physical properties of the coating.

[0049] In an optional embodiment, when the coating includes a first sub-coating and a second sub-coating stacked in sequence in a direction away from the transfer substrate, the molar ratio of the cross-linking agent to the block copolymer in the first sub-coating is 0.15-0.3 (for example, 0.15, 0.20, 0.25, 0.30), and the molar ratio of the cross-linking agent to the block copolymer in the second sub-coating is 0.05-0.15 (for example, 0.05, 0.10, 0.12, 0.15).

[0050] In an optional embodiment, when the coating includes a first sub-coating, a third sub-coating, and a second sub-coating stacked in sequence along a direction away from the transfer substrate, the molar ratio of the cross-linking agent to the block copolymer in the first sub-coating is 0.2-0.3 (for example, 0.20, 0.22, 0.25, 0.30), the molar ratio of the cross-linking agent to the block copolymer in the third sub-coating is 0.1-0.2 (for example, 0.1, 0.13, 0.15, 0.18, 0.20), and the molar ratio of the cross-linking agent to the block copolymer in the second sub-coating is 0.05-0.1 (for example, 0.05, 0.08, 0.1).

[0051] In some embodiments, the adhesive comprises an aminosilane adhesive.

[0052] The aminosilane adhesive has a molecular structure of aminosilane, which enables it to generate bonding force with polar and non-polar materials at the same time and has good bonding performance. Specifically, the aminosilane adhesive includes one or two of γ-aminopropyltriethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.

[0053] In some embodiments, the thickness of the bonding layer is 0.1-1 μm, and the thickness of the coating layer is 5-15 μm.

[0054] The bonding layer is located between the transfer substrate and the coating, and is used to bond the coating to the transfer substrate to prevent the coating from detaching from the transfer substrate when the viscosity of the coating decreases; if the thickness of the bonding layer is too small, the coating cannot be firmly bonded to the transfer substrate; if the thickness of the bonding layer is too large, it will affect the formation of the gate line and cause material waste, so the thickness of the bonding layer is controlled to be 0.1-1μm. The coating is used to freely bond or release the electrode slurry, and needs to have a reversible viscosity; if the thickness of the coating is too small, it cannot achieve the required viscosity and is difficult to bond the electrode slurry; if the thickness of the coating is too large, it will affect the formation of the gate line and cause material waste, so the thickness of the coating is controlled to be 5-15μm. In an optional embodiment, the coating includes at least a first sub-coating and a second sub-coating, the first sub-coating is used to contact the bonding layer, the thickness of the first sub-coating can be 1-6μm, the second sub-coating is used to bond the electrode slurry, the thickness of the second sub-coating can be 1-5μm; a third sub-coating as a transition layer can also be included between the first sub-coating and the second sub-coating, and the thickness of the third sub-coating can be 1-5μm.

[0055] The present application embodiment provides a pattern transfer method, comprising: S100: Provide pattern transfer plate, such as Figure 1 to Figure 2 As shown, the pattern transfer plate includes a transfer substrate 10 having a plurality of receiving grooves 11, and an adhesive layer 20 and a coating layer 30 sequentially stacked in the receiving grooves 11; the adhesive layer 20 includes an adhesive; the coating layer 30 includes a temperature-controlled viscosity reversible material; the temperature-controlled viscosity reversible material includes a block copolymer, a crosslinking agent and a free radical initiator; the molar ratio of the crosslinking agent to the free radical initiator in the coating layer 30 gradually increases in a direction away from the transfer substrate 10; the block copolymer includes a block copolymer containing a poly (ethylene oxide-propylene oxide-ethylene oxide) group; the crosslinking agent includes an organic acid ester containing a disulfide bond; S200: heating the coating 30 to 80° C.-100° C. to increase the viscosity of the coating 30; S300: Figure 1 As shown, the electrode slurry 40 is filled into the receiving tank 11 having the coating 30 on the surface; S400: Figure 3 As shown, the pattern transfer plate filled with the electrode slurry 40 is inverted on the substrate 50 , the coating 30 is heated to above 120° C. to reduce the viscosity of the coating 30 , and the electrode slurry 40 in the receiving tank 11 is transferred to the substrate 50 .

[0056] In the pattern transfer method in the embodiment of the present application, when the coating is heated to 80°C-100°C, the free radical initiator releases free radicals, thereby promoting the cross-linking reaction between the organic acid ester containing disulfide bonds (-SS-) and the block copolymer containing poly (ethylene oxide-propylene oxide-ethylene oxide) groups to form a three-dimensional network structure, which increases the viscosity of the coating and solidifies the coating. Then the electrode slurry is filled in the receiving tank so that the electrode slurry is bonded by the coating. After the pattern transfer plate filled with the electrode slurry is inverted on the substrate, the temperature is continued to rise to above 120°C, the disulfide bonds (-SS-) of the organic acid ester containing disulfide bonds are broken, the three-dimensional network structure is de-crosslinked, and the viscosity of the coating is reduced. Due to the dual effects of the reduced viscosity of the coating and the weight of the electrode slurry itself, the electrode slurry is transferred from the receiving tank to the substrate; after this pattern transfer or before the next pattern transfer, the coating is cooled again to 80°C-100°C to increase the viscosity of the coating again, thereby achieving reversible viscosity.

[0057] In an optional embodiment, during the process of heating the coating, a hot circulating air heating device, an infrared filament heating device, or an infrared LED device may be used to heat the coating.

[0058] Using these heating devices to heat the coating can not only heat the coating quickly and evenly, but also facilitate the installation and modification of equipment in the battery electrode process.

[0059] In some embodiments, when the coating is at 80°C-100°C, the viscosity of the coating is 100-500 Pa·s; When the coating is at a temperature above 120°C, the viscosity of the coating is 10-50 Pa·s.

[0060] When the temperature of the coating is lower than 80℃, the viscosity of the coating is relatively low, about 10-50Pa·s. When the temperature of the coating is greater than 100℃ and less than 120℃, the viscosity of the coating is not much different from the viscosity when the temperature is 80℃-100℃, about 100-500Pa·s. When the temperature of the coating reaches 120℃, the viscosity of the coating drops rapidly (in 2-5s) to 10-50Pa·s.

[0061] The embodiment of the present application provides a solar cell, including a grid electrode, the grid electrode is prepared using the pattern transfer plate in any of the above embodiments, and / or the grid electrode is prepared by the pattern transfer method in any of the above embodiments. The advantages of the above pattern transfer plate or pattern transfer method are also possessed by the perovskite solar cell, which will not be repeated here.

[0062] The following specific examples further illustrate the present application, but should not be construed as limiting the present application. Without departing from the spirit and substance of the present application, modifications or replacements made to the methods, steps or conditions of the present application are within the scope of the present application.

[0063] Example 1 like Figure 2 As shown, the pattern transfer plate of Example 1 includes: The transfer substrate 10 has a plurality of receiving grooves 11; the receiving grooves 11 are used to receive the electrode slurry 40; The adhesive layer 20 and the coating layer 30 are sequentially stacked on the surface of the receiving groove 11; The coating 30 includes a first sub-coating 31, a third sub-coating 33 and a second sub-coating 32 which are sequentially stacked in a direction away from the transfer substrate 10; Wherein, the bonding layer 20 includes a bonding agent; the coating 30 includes a temperature-controlled viscosity reversible material; The temperature-controlled viscous reversible material includes a block copolymer, a cross-linking agent, and a free radical initiator; Block copolymers include poly(styrene-isoprene-styrene)-poly(ethylene oxide-propylene oxide-ethylene oxide) block copolymers; Cross-linking agents include disulfide-containing diacrylates and disulfide-containing dibutyl acrylates; Free radical initiators include azobisisobutyronitrile and azobisisoheptanenitrile; In the first sub-coating 31 , the molar ratio C11 of the crosslinking agent to the free radical initiator is 11.5, and the molar ratio C12 of the crosslinking agent to the block copolymer is 0.3; In the third sub-coating 33, the molar ratio C31 of the crosslinking agent to the free radical initiator is 16, and the molar ratio C32 of the crosslinking agent to the block copolymer is 0.16; In the second sub-coating 32, the molar ratio C21 of the crosslinking agent to the free radical initiator is 28, and the molar ratio C22 of the crosslinking agent to the block copolymer is 0.08; The binder is γ-aminopropyltriethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane; The thickness of the adhesive layer 20 is 0.5 μm, and the thickness of the coating layer 30 is 10 μm.

[0064] The pattern transfer method of embodiment 1 comprises: S110: providing the pattern transfer plate of Example 1; S210: heating the coating 30 to 90° C. to increase the viscosity of the coating 30; S310: Figure 1 As shown, the electrode slurry 40 is filled into the receiving tank 11 having the coating 30 on the surface; S410: Figure 3 As shown, the pattern transfer plate filled with the electrode slurry 40 is inverted on the substrate 50, the coating 30 is heated to 125°C to reduce the viscosity of the coating 30, and the electrode slurry 40 in the receiving tank 11 is transferred to the substrate 50; S510: Sintering the electrode slurry 40 transferred to the substrate 50 to form metal grid lines, thereby obtaining a solar cell.

[0065] Example 2-Example 8 The pattern transfer plates of Examples 2 to 8 are similar in structure to the pattern transfer plates of Example 1, except that the formulas of the bonding layer and the coating in the pattern transfer plates of Examples 2 to 8 are different, and the formulas of the bonding layer and the coating in Examples 2 to 8 are shown in Table 1. The solar cells of Examples 2 to 8 were prepared with reference to the pattern transfer method of Example 1, except that the electrode slurry was transferred to the substrate using the pattern transfer plates of Examples 2 to 8, respectively.

[0066] Table 1

[0067] It should be noted that the coating in Examples 3 and 7 of the present application only includes the first sub-coating and the second sub-coating, and does not include the third sub-coating. Therefore, C31-C32 in Examples 3 and 7 do not have numerical values.

[0068] In order to more clearly illustrate the technical effects of the embodiments of the present application, the present application also points out the solar cell of comparative example 1.

[0069] Comparative Example 1 In Comparative Example 1, the electrode slurry is transferred to the substrate by using the conventional screen printing technology, and the metal grid lines are formed by sintering to obtain a solar cell.

[0070] The heterojunction solar cells of Examples 1-8 of the present application and Comparative Example 1 are respectively prepared into photovoltaic modules, and the performance of the photovoltaic modules is tested to obtain the open circuit voltage Voc, short circuit current density Jsc, fill factor FF, and photoelectric conversion efficiency Eta of the corresponding photovoltaic modules. The test results are shown in Table 2.

[0071] Table 2

[0072] It can be seen from Table 2 that compared with Comparative Example 1, the short-circuit current density, fill factor and photoelectric conversion efficiency of the heterojunction solar cells of Examples 1-8 of the present application are improved; among them, the short-circuit current density can be increased by 0.526 mA / cm², the fill factor can be increased by 0.326%, and the photoelectric conversion efficiency can be increased by 0.334%.

[0073] In summary, in the embodiment of the present application, the pattern transfer plate includes an adhesive layer formed by an adhesive and a coating formed by a temperature-controlled viscous reversible material. The adhesive layer is located between the transfer substrate and the coating, and the adhesive layer can strengthen the bonding effect between the transfer substrate and the coating, and prevent the coating from detaching from the transfer substrate after the polymer in the coating is de-crosslinked. The viscosity of the coating is affected by temperature, and the viscosity reversible performance is achieved by regulating the temperature of the coating, so that not only the coating can be recycled, but also the prepared grid line is of good quality, breaking through the grid line width limit prepared by the current process, achieving a better aspect ratio, reducing the shading area, improving the battery conversion efficiency, reducing the slurry consumption, and no need to use a specific transparent transfer carrier material as a substrate.

[0074] The embodiment of the present application can provide a photovoltaic module, including the solar cell in any of the above embodiments. The photovoltaic module also has the advantages of the above photovoltaic solar cell, which will not be repeated here.

[0075] The embodiment of the present application can provide a photovoltaic system, including the photovoltaic module in any of the above embodiments. The advantages of the above photovoltaic modules are also possessed by the photovoltaic system, which will not be repeated here. The above photovoltaic system has a wide range of applications, not only limited to photovoltaic power stations, such as ground power stations, rooftop power stations and water power stations, but also includes various equipment and devices that use solar energy to generate electricity, such as user solar power supplies, solar street lights, solar cars and solar buildings. Of course, it can be understood that the application scenarios of the photovoltaic system are not limited to this, that is to say, the photovoltaic system can be used in all fields where solar energy is required for power generation. Taking the photovoltaic power generation system network as an example, the photovoltaic system may include a photovoltaic array, a junction box and an inverter. The photovoltaic array may be an array combination of multiple photovoltaic modules. For example, multiple photovoltaic modules may form multiple photovoltaic arrays. The photovoltaic array is connected to a junction box. The junction box can converge the current generated by the photovoltaic array. The converged current flows through the inverter and is converted into the alternating current required by the mains power grid, and then connected to the mains network to realize solar power supply.

[0076] It should be noted that the terms "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc. are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. The orientation words "inside" and "outside" refer to the inside and outside relative to the outline of each component itself. For example, if the device in the accompanying drawings is inverted, the device described as "above other devices or structures" or "above other devices or structures" will be positioned as "below other devices or structures" or "below other devices or structures". Therefore, the exemplary term "above..." can include both "above..." and "below..." orientations. The device can also be positioned in other different ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used here are interpreted accordingly.

[0077] It should also be noted that "one embodiment", "another embodiment", "embodiment", etc. mentioned in this application refer to the specific features, structures or characteristics described in conjunction with the embodiment included in at least one embodiment generally described in this application. The same expression appearing in multiple places in the specification does not necessarily refer to the same embodiment. Further, when describing a specific feature, structure or characteristic in conjunction with any embodiment, it is claimed that the realization of such feature, structure or characteristic in conjunction with other embodiments also falls within the scope of this application.

[0078] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0079] It should also be noted that the above are only preferred embodiments of the present application, and the patent protection scope of the present application is not limited thereto. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A pattern transfer plate, characterized in that: include: A transfer substrate, wherein the transfer substrate has a plurality of receiving grooves; The containing tank is used to contain electrode slurry; An adhesive layer, the adhesive layer being located on the surface of the receiving groove; The bonding layer includes a bonding agent; A coating, the coating being located on the surface of the bonding layer; the coating comprising a temperature-controlled viscosity reversible material; The temperature-controlled viscous reversible material includes a block copolymer, a crosslinking agent and a free radical initiator; the molar ratio of the crosslinking agent to the free radical initiator in the coating gradually increases in a direction away from the transfer substrate; the block copolymer includes a block copolymer containing a poly (ethylene oxide-propylene oxide-ethylene oxide) group; and the crosslinking agent includes an organic acid ester containing a disulfide bond.

2. The pattern transfer plate according to claim 1, characterized in that: The coating layer at least comprises a first sub-coating layer and a second sub-coating layer stacked in sequence in a direction away from the transfer substrate; The molar ratio of the crosslinking agent to the free radical initiator in the first sub-coating layer is smaller than the molar ratio of the crosslinking agent to the free radical initiator in the second sub-coating layer.

3. The pattern transfer plate according to claim 1, characterized in that: The coating comprises a first sub-coating, a third sub-coating, and a second sub-coating which are sequentially stacked in a direction away from the transfer substrate; wherein the molar ratio of the crosslinking agent to the free radical initiator in the first sub-coating is less than the molar ratio of the crosslinking agent to the free radical initiator in the third sub-coating; The molar ratio of the crosslinker to the free radical initiator in the third sub-coating is less than the molar ratio of the crosslinker to the free radical initiator in the second sub-coating.

4. The pattern transfer plate according to any one of claims 1 to 3, characterized in that: The block copolymer containing poly(ethylene oxide-propylene oxide-ethylene oxide) groups includes poly(styrene-isoprene-styrene)-poly(ethylene oxide-propylene oxide-ethylene oxide) block copolymer.

5. The pattern transfer plate according to any one of claims 1 to 3, characterized in that: The disulfide bond-containing organic acid ester includes one or both of disulfide bond-containing diacrylate and disulfide bond-containing dibutyl acrylate.

6. The pattern transfer plate according to any one of claims 1 to 3, characterized in that: The free radical initiator includes one or both of azobisisobutyronitrile and azobisisoheptanenitrile.

7. The pattern transfer plate according to any one of claims 1 to 3, characterized in that: The temperature-controlled viscosity reversible material further includes an aminosilane coupling agent.

8. The pattern transfer plate according to claim 7, characterized in that: The aminosilane coupling agent includes one or two of γ-aminopropyltriethoxysilane and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.

9. The pattern transfer plate according to any one of claims 1 to 3, characterized in that: The molar ratio of the crosslinking agent to the block copolymer is 0.05-0.

3.

10. The pattern transfer plate according to any one of claims 1 to 3, characterized in that: The adhesive includes an aminosilane adhesive.

11. The pattern transfer plate according to any one of claims 1 to 3, characterized in that: The thickness of the bonding layer is 0.1-1 μm, and the thickness of the coating is 5-15 μm.

12. A pattern transfer method, characterized in that: include: A pattern transfer plate is provided, the pattern transfer plate comprising a transfer substrate having a plurality of receiving grooves, and a bonding layer and a coating layer sequentially stacked in the receiving grooves; the bonding layer comprises a bonding agent; the coating layer comprises a temperature-controlled viscosity reversible material; the temperature-controlled viscosity reversible material comprises a block copolymer, a crosslinking agent and a free radical initiator; the molar ratio of the crosslinking agent to the free radical initiator in the coating layer gradually increases in a direction away from the transfer substrate; the block copolymer comprises a block copolymer containing a poly(ethylene oxide-propylene oxide-ethylene oxide) group; the crosslinking agent comprises an organic acid ester containing a disulfide bond; Heating the coating to 80° C.-100° C. to increase the viscosity of the coating; Filling the electrode slurry into the containing tank having the coating on the surface; The pattern transfer plate filled with the electrode slurry is inverted on the substrate, the coating is heated to above 120° C. to reduce the viscosity of the coating, and the electrode slurry in the containing tank is transferred to the substrate.

13. The pattern transfer method according to claim 12, characterized in that: When the coating is at 80°C-100°C, the viscosity of the coating is 100-500 Pa·s; When the coating is at a temperature of 120° C. or higher, the viscosity of the coating is 10-50 Pa·s.

14. A solar cell, characterized in that: The solar cell comprises a grid line electrode, wherein the grid line electrode is prepared using the pattern transfer plate according to any one of claims 1 to 11, and / or the grid line electrode is prepared by the pattern transfer method according to any one of claims 12 to 13.

Citation Information

Patent Citations

  • Method and device for printing metal electrode on front side of battery piece

    CN103730542A

  • Pattern transfer sheet and method using release layer and / or paste mixture

    CN116001465A

  • Transfer printing device and preparation method thereof, thin film transfer printing method, light-emitting device and preparation method thereof

    CN118269470A

  • Pattern transfer sheet, paste filling unit, and photovoltaic solar cell

    CN218020905U

  • Transfer device and solar cell

    CN221584783U